Dynamics and microrheology of colloidal clay-polymer glasses and gels: Size-dependent phenomena and re-entrant behavior at early aging times - Shen, Jiachun; Bhatia, Surita R. (The Journal of chemical physics, 2023)
Colloidal clay Laponite forms a variety of arrested states that display interesting aging behavior. Microrheology has been applied to Laponite-based glasses and gels, but few studies evaluate the influence of probe particle size. In this work, we report the dynamics and microrheology of Laponite-polymer dispersions during aging using passive microrheology with three different probe particle sizes. At early aging times, the neat Laponite dispersion forms an arrested state; the nature of this state (e.g., a repulsive glass or gel) has remained the subject of debate. The addition of polymer retards gelation and melts the arrested state. While this melting has been observed at the macroscale and has been attributed to a re-entrant transition of a repulsive glass to a liquid state, to our knowledge, it has not been observed at the microscale. The delay of the gelation time needed to form an arrested state was found to depend on the polymer concentration and could vary from ∼24 h for neat Laponite to seven days for some Laponite-polymer samples. Significant effects of probe particle sizes are observed from the mean-squared displacement (MSD) curves as small and intermediate probe particles show diffusive motion, while the motion of large particles is restricted. By examining the factor of ⟨Δr2 (τ)⟩a, structural heterogeneity can be confirmed through the strong size-dependence displayed. Different MSD trends of probe particles are obtained at longer aging times, but no significant changes occur after 30 days of aging. Our microrheology results also reveal significant effects of probe particle size.